The effectiveness of an empathy training program in increasing the level and degree of empathy of fourth year nursing students - Ruiz, Ma. Pilar M. (Animo Repository, 1986)
The study aimed to find out the effectiveness of an Empathy training program in increasing the empathy level and degree of fourth year nursing students. The Experimental Pretest-Posttest Control Group Design was used in this study. The subjects were 18 fourth year nursing students randomly selected from among the 85 total populations and assigned to two groups: the experimental group who underwent a 16-hour empathy training program, and the control group, who did not undergo training. Two instruments were used: the Nurses' Empathy Level Questtionnaire constructed by the researcher and measured by Gazda's Empathy Scale, and the La Monica -- revised Empathy Construct Rating Scale. The data were treated by the use of t-tests. To find out whether a significant difference exist between the pretest and posttest results of the experimental and control groups in levels and degrees of empathy, the t-test for independent samples was used on the NELQ and the ECRS. To determine any significant difference on the posttest gain scores of the experimental and the control groups on the NELQ and the ECRS, the t-test for independent samples was used. The NELQ was rated by three raters using Gazda's Empathy Scale. The interrater reliability was very high for both pretest and posttest rating (.96). The results yielded by this study, t=9.941 (df=8, p .001) in the NELQ and t=5.90 (df=8, p .05) on the ECRS, indicate that the Empathy Training Program was very effective in helping the Nursing students who underwent the training to increase their levels and degrees of empathy therefore helping them to communicate more empathically.